Medpoklicno izobraževanje zaposlenih v nujni medicinski pomoči - Železnjak, Vladka (Obzornik zdravstvene nege, 2016)
Introduction: Education system preparing people for work in an emergency medical service team in Slovenia is insufficient and needs changes. The aim of the study was to define which theoretical knowledge and practical skills should be acquired by members of all professional teams both during formal learning and in the course of their work as part of the emergency medical service. Methods: Triangulation of methods was used in the research. The qualitative method with semi-structured interview was used to collect data from a sample of 30 employees of the emergency medical service team, and the Delphi method was used to aggregate and coordinate the opinions of 27 respondents on the proposed measures in seven subject areas. The respondents were divided into three groups: emergency medical service employees, heads of emergency medical service, and healthcare policy makers. The Delphi method was carried out in two rounds. Results: According to the research participants, the knowledge and skills relevant for emergency medical service work they gained during formal schooling was insufficient. They also claim that appropriate changes in the education system, together with inter-professional education both during formal learning and during work, would render the emergency medical service system more efficient. Discussion and conclusion: The emergency medical service experts participating in the research suggest the translation of best practices from other organisational and educational models into education system, the implementation of team clinical training in emergency medicine and the initiation of interprofessional education based on simulation scenarios for all emergency medical service professional teams.
Keywords: interprofessional collaboration; medpoklicno sodelovanje; nujna medicinska pomoč; team training; team work; timsko delo; timsko izobraževanje